Five years of observations of the GREMPA almond collection in CEBAS-CSIC, Murcia, Spain - Dicenta F.; Egea J.; Berenguer T. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
The GREMPA (Groupe de Recherches et d'Etudes Méditerranéennes pour l'Amandier et le Pistachier) agreed to establish an almond collection, including 35 new European selections, in the different GREMPA countries in order to study their behaviour in each of these countries. This collection consisted of 13 cultivars from France, 10 from Spain, 7 from Italy and 5 from Greece. The collection was established in CEBAS-CSIC, Murcia, Spain, in 1992. From 1994 to 1998, different traits were studied (flowering, production, fruit characteristics, etc). In 1999, most of the trees were removed from the orchard and 12 selections were kept because of their good behaviour.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)